Efficient Comparative Analysis Of Fertilizers Palm Oil - Bayu Febriadi; Anisya Anisya; Pandu Pratama Putra (IJISTECH (International Journal of Information System and Technology), 2019)
Palm oil is a vegetable oil-producing plant that has more advantages compared to other vegetable oil-producing plants, which have high productivity reaching 4 tons ha-1 Crude Palm Oil (CPO). Palm oil is also a raw material for making food and non-food ingredients, and renewable fuels. The author wants to make an analysis by comparing two methods, namely the AHP Method (Analytical Hierarchy Process) and Fuzzy logic which is able to handle the uncertainty and uncertainty used. Fuzzy logic used is the Fuzzy Tsukamoto inference system because this method uses monotonous value applications, the output of the inference output from each rule is explicitly given (crisp) based on α-predicate (fire strength). Whereas the AHP Method can facilitate in calculating the validity to the tolerance level of concentration as criteria and alternatives chosen by the user.